2018
DOI: 10.1080/07391102.2018.1461134
|View full text |Cite
|
Sign up to set email alerts
|

Study on the binding characteristics of hydroxylated polybrominated diphenyl ethers and thyroid transporters using the multispectral technique and computational simulation

Abstract: Hydroxylated polybrominated diphenyl ethers (OH-PBDEs) are a class of toxic environmental pollutants that are persistent, bioaccumulative, and difficult to degrade. Their structure is very similar to the thyroid hormone (T4) and uses the body's thyroid transporter (TTR) binding to interfere with the endocrine balance, disrupting the body's normal physiological activity. According to Fourier transform infrared spectroscopy and dynamics simulation of do_dssp module analysis, there are three kinds of OH-PBDEs tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Moreover, it is suggested that the presence of hydroxyl group in PBDEs affects the binding ability between THs and TTR, leading to increased FTHs, such as 3-OH-BDE-47 and 6-hydroxy-2,2′,4,4′-tetrabromodiphenyl ether (6-OH-BDE-47) . Molecular docking analysis has shown that 4 hydroxy-2,2′,3,4,5,5′,6-heptabromodiphenyl ether (4-OH-BDE-187) is bonded to TTR by hydrogen bonds to form stable complexes . Additionally, PBDE sulfates and OH-PBDEs can bind to TBG and TTR, as well as two subtypes of nuclear TRs, exhibiting an agonistic effect on the TR signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is suggested that the presence of hydroxyl group in PBDEs affects the binding ability between THs and TTR, leading to increased FTHs, such as 3-OH-BDE-47 and 6-hydroxy-2,2′,4,4′-tetrabromodiphenyl ether (6-OH-BDE-47) . Molecular docking analysis has shown that 4 hydroxy-2,2′,3,4,5,5′,6-heptabromodiphenyl ether (4-OH-BDE-187) is bonded to TTR by hydrogen bonds to form stable complexes . Additionally, PBDE sulfates and OH-PBDEs can bind to TBG and TTR, as well as two subtypes of nuclear TRs, exhibiting an agonistic effect on the TR signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…206 Molecular docking analysis has shown that 4 hydroxy-2,2′,3,4,5,5′,6-heptabromodiphenyl ether (4-OH-BDE-187) is bonded to TTR by hydrogen bonds to form stable complexes. 207 Additionally, PBDE sulfates and OH-PBDEs can bind to TBG and TTR, 208 as well as two subtypes of nuclear TRs, exhibiting an agonistic effect on the TR signaling pathway. 209 Similar with PFASs, the binding of PBDEs with TH-related proteins contributes to the aggregation of FTHs.…”
Section: Hyperthyroidism Risk Chemicalsmentioning
confidence: 99%
“… Fourier transform infrared spectroscopy and dynamics simulation combined with thermodynamic analysis suggested that 4′‐OH‐BDE‐49, 4‐OH‐BDE‐187 and 4‐OH‐BDE‐188 induce changes in TTR secondary structure by altering the internal microenvironment of TTR. OH‐PBDEs bind to TTR mainly by hydrophobic interaction, inducing changes in TTR secondary structure (Wei et al., 2019 ). Molecular docking simulations indicated that 4′‐OH‐BDE‐49 and 4‐OH‐BDE‐188 have non‐covalent cationic–π interactions with TTR, whereas 4‐OH‐BDE‐187 was bonded to TTR by hydrogen bonds and van der Waals force.…”
Section: Assessmentmentioning
confidence: 99%
“…Molecular docking simulations indicated that binding of OH‐PBDEs to TTR was mostly by hydrophobic interactions but that positively charged Lys15 was important for the coordination. – Fourier transform infrared spectroscopy and dynamics simulation combined with thermodynamic analysis suggested that 4′‐OH‐BDE‐49, 4‐OH‐BDE‐187 and 4‐OH‐BDE‐188 induce changes in TTR secondary structure by altering the internal microenvironment of TTR. OH‐PBDEs bind to TTR mainly by hydrophobic interaction, inducing changes in TTR secondary structure (Wei et al., 2019). Molecular docking simulations indicated that 4′‐OH‐BDE‐49 and 4‐OH‐BDE‐188 have non‐covalent cationic–π interactions with TTR, whereas 4‐OH‐BDE‐187 was bonded to TTR by hydrogen bonds and van der Waals force. – Spectroscopic analysis indicated that OH‐PBDEs bind to the T4 binding site of TTR (Ren & Guo, 2012).…”
Section: Assessmentmentioning
confidence: 99%
“…Through a series of comprehensive analyses, the research unveiled significant alterations in the microenvironment and secondary structure of BSA upon exposure to PVC MPs. 6 Wei and colleagues 7 meticulously explored the impact of hydroxylated polybrominated diphenyl ethers (OH-PBDEs) as hazardous environmental contaminants on the thyroid transporter (TTR). Computational simulations revealed that OH-BDE induced notable modifications within the internal milieu of TTR, consequently precipitating alterations in its secondary structural attributes.…”
Section: ■ Introductionmentioning
confidence: 99%